2008
DOI: 10.1111/j.1462-5822.2007.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Shiga toxin 1 induces apoptosis through the endoplasmic reticulum stress response in human monocytic cells

Abstract: SummaryShiga toxins (Stxs) expressed by the enteric pathogens Shigella dysenteriae 1 and enterohaemorrhagic Escherichia coli are potent protein synthesis inhibitors. Shiga toxins have also been shown to induce apoptosis in epithelial, endothelial and monocytic cells. The precise relationship between protein synthesis inhibition and induction of apoptosis is not known. We show that stimulation of the myelogenous leukaemia cell line THP-1 with purified Stx1 induced the endoplasmic reticulum (ER) stress response.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
184
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(195 citation statements)
references
References 33 publications
8
184
3
Order By: Relevance
“…Gb3Cer-and Gb4Cer-negative Jurkat and HL-60 cell lines were resistant, whereas Raji (Gb3Cer-positive) and THP-1 cells (Gb3Cer-and Gb4Cer-positive) were susceptible to Stx2, as expected from toxin treatment studies of THP-1 cells performed by others (98)(99)(100). However, THP-1 cells exhibited a rather moderate but signifi cant susceptibility toward Stx2 when compared with resistant Jurkat and HL-60 cells, although a more pronounced cytotoxicity has been reported for THP-1 cells using Stx1 ( 101 ).…”
Section: Discussionsupporting
confidence: 58%
“…Gb3Cer-and Gb4Cer-negative Jurkat and HL-60 cell lines were resistant, whereas Raji (Gb3Cer-positive) and THP-1 cells (Gb3Cer-and Gb4Cer-positive) were susceptible to Stx2, as expected from toxin treatment studies of THP-1 cells performed by others (98)(99)(100). However, THP-1 cells exhibited a rather moderate but signifi cant susceptibility toward Stx2 when compared with resistant Jurkat and HL-60 cells, although a more pronounced cytotoxicity has been reported for THP-1 cells using Stx1 ( 101 ).…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, the pathogen minimally employs Ank9 to invoke ER stress while also utilizing Ank4 to modulate the ensuing UPR and ERAD to bolster its growth. Other intracellular bacterial effectors, including Brucella species TcpB and Listeria monocytogenes listeriolysin O, and extracellular bacterial toxins, such as Vibrio cholerae cholera toxin and Escherichia coli subtilase and Shiga toxin 1, induce the UPR and/or ER morphological changes (10,(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71). To our knowledge, Ank4 stands unique as the only bacterial protein identified thus far that modulates ERAD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the triggering of apoptosis could actually be part of the innate host defense system to prevent chronic infection by these organisms. In this regard, there is evidence that intracellular organisms activate the UPR as a mechanism to support synthesis of pathogen proteins (41)(42)(43), and these organisms also display PAMPs that can activate scavenger receptors and TLRs. Most interestingly, in vitro studies have shown that macrophage apoptosis is associated with control of infection by M. tuberculosis (40), and genetic studies in mice have shown an association between resistance to infection by M. tuberculosis and induction of macrophage apoptosis (44).…”
Section: The Roles Of Er Stress and Pattern Recognition Receptors In mentioning
confidence: 99%